1966
DOI: 10.1111/j.1438-8677.1966.tb00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Numbers of Some Flowering Plants of Spain and S. France

Abstract: The chromosome numbers of 32 plant species from Spain and S. France, all collected in natural habitats, were determined. Voucher specimens have been deposited in the Utrecht Herbarium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1
1

Year Published

1971
1971
1986
1986

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 19 publications
1
7
1
1
Order By: Relevance
“…The numbers 2n = 59, counted in French material (GADELLA et al 1966) and 2n = 42 in North African material (REESE 1957), were not found in our French material. GADELLA et al counted 2n = 64 in Spanish material.…”
Section: Salvia Verbenaca Lcontrasting
confidence: 61%
“…The numbers 2n = 59, counted in French material (GADELLA et al 1966) and 2n = 42 in North African material (REESE 1957), were not found in our French material. GADELLA et al counted 2n = 64 in Spanish material.…”
Section: Salvia Verbenaca Lcontrasting
confidence: 61%
“…3 mm x I mm, inner side leveled or oblique at apex, bearing a transverse ridge near apex or in middle. Murley (1951) (Gadella and Kliphuis 1966;Curran 1968). Baez-Major (1934 County, Ontario claim that this plant will taint milk.…”
mentioning
confidence: 99%
“…Vicia hirsuta has for long been the object of cytological studies which, however, were mainly limited to the determination of chromosome numbers (SVECHNIKOVA 1927;KAWAKAMI 1930;HEITZ 1930;ROHWEDER 1937;SENN 1938;LovE andLovE 1956, CINCURA 1962;SRIVASTAVA 1963;HuZIWARA and KoNDO 1963;TATUNO and KoDAMA 1965;GADELLA and KLIPHUS 1966;KoDAMA 1967;KozuHAROV et al 1972;MARKOVA 1972;YAMAMOTO 1973;SAREEN and TREHAN 1976;KuzMANOV 1978).…”
Section: Introductionmentioning
confidence: 99%